2018
DOI: 10.1017/s0025315418000127
|View full text |Cite
|
Sign up to set email alerts
|

New report of malformations in blue shark embryos (Prionace glauca) from the western coast of Baja California Sur, Mexico

Abstract: Four new malformations observed in blue shark embryos in the western coast of Baja California Sur, Mexico are reported in this study. The embryos of blue shark samples were obtained on board the industrial fishing boat ‘Damasta’; the organisms were frozen and transferred to CIBNOR Fish Ecology Laboratory where the corresponding measurements were taken and malformations observed. The first malformation was the presence of one nostril in two female embryos that showed short and crushed snouts. The second one was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…However, similar reports in the South Atlantic Ocean are less frequent in comparison with the North Atlantic Ocean. In both the Atlantic and Pacific Oceans, the most commonly reported malformations for this species at this stage of development are diprosopia (usually two heads) and twisted vertebral columns (Mancini et al ., 2006; Bejarano-Álvarez et al ., 2011; Galván-Magaña et al ., 2011; Hevia-Hormazábal et al ., 2011; Ehemann et al ., 2016; Lamarca et al ., 2017; Pastén-Marambio et al ., 2018; Rodriguez-Romero et al ., 2019; Ramírez-Amaro et al ., 2019; Kanagusuku et al ., 2020). In this study, we report the second embryo with a kind of cyclopia for the South-western Atlantic Ocean (Ferreira et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, similar reports in the South Atlantic Ocean are less frequent in comparison with the North Atlantic Ocean. In both the Atlantic and Pacific Oceans, the most commonly reported malformations for this species at this stage of development are diprosopia (usually two heads) and twisted vertebral columns (Mancini et al ., 2006; Bejarano-Álvarez et al ., 2011; Galván-Magaña et al ., 2011; Hevia-Hormazábal et al ., 2011; Ehemann et al ., 2016; Lamarca et al ., 2017; Pastén-Marambio et al ., 2018; Rodriguez-Romero et al ., 2019; Ramírez-Amaro et al ., 2019; Kanagusuku et al ., 2020). In this study, we report the second embryo with a kind of cyclopia for the South-western Atlantic Ocean (Ferreira et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Within the last two decades, reports of abnormalities in elasmobranch embryos have increased worldwide, and a wide variety of abnormal morphological conditions have been described. The reports come from a range of seas and oceans, including the Atlantic Ocean (Clark, 2002; Coelho & Erzini, 2006; Mancini et al ., 2006; Delpiani et al ., 2011; Zaera & Johnsen, 2011; Wagner et al ., 2013; Dos Santos & Gadig, 2014; Afonso et al ., 2016; Lamarca et al ., 2017; Ramírez-Amaro et al ., 2019; Prado et al ., 2020), Pacific Ocean (Goto et al ., 1981; Clark, 2002; Bejarano-Álvarez et al ., 2011; Galván-Magaña et al ., 2011; Hevia-Hormazábal et al ., 2011; Bejarano-Álvarez & Galvãn-Magaña, 2013; Muñoz-Osorio, et al ., 2013; Escobar-Sanchez et al ., 2014; Becerril-García et al ., 2017; Pastén-Marambio et al ., 2018; Rodriguez-Romero et al ., 2019), Mediterranean Sea (Saidi et al ., 2006; Bottaro et al ., 2008; Sans-Coma et al ., 2016), Caribbean (Ehemann et al ., 2016) and Indian Ocean (Moore, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reports include albinism (e.g., Clark, 2002;Saïdi et al, 2006;Bottaro et al, 2008;Escobar-Sánchez et al, 2014), bicephaly (e.g., Galván-Magaña et al, 2011;Wagner et al, 2013), diprosopia (e.g., Mancini et al, 2006;Hevia-Hormazábal et al, 2011;Driggers et al, 2012), deformities in axial skeleton (e.g., Pastore & Prato, 1989;Heupel et al, 1999;Mancini et al, 2006), mummification (e.g., Rosa-Molinar et al, 1983;Sandoval-Castillo & Villavicencio-Garay-Zar, 2008) and even cyclopia (Bejarano-Álvarez & Galván-Magaña, 2013). Blue shark (Prionace glauca) is the shark species with the highest number of anomalies reported, which have been described by different authors (e.g., Goto et al, 1981;Mancini et al, 2006;Galván-Magaña et al, 2011;Hevia-Hormazábal et al, 2011;Bejarano-Álvarez et al, 2013;Ehemann et al, 2016;Rodríguez-Romero et al, 2018;Ramírez-Amaro et al, 2019).…”
mentioning
confidence: 99%
“…Another factor that can be affecting the malformation presence is environmental degradation or pollution (Goto et al, 1981;Ferreira et al, 2002;Rosa et al, 2004;Mancini et al, 2006). In this context, some studies have been reported presence of high levels of heavy metals (e.g., Hg) ( Barrera-García et al, 2012;Rodríguez-Romero et al, 2018) and genetic alterations related with initial stages of development (Mancini et al, 2006;Rodríguez-Romero et al, 2018). Although the lack of information about the causes of anomalies, an explanation for some individual reported in this study who did not survive after birth, could be related with difficulties in swimming, feeding and avoiding predators in these individuals (Mancini et al, 2006;Rodríguez-Romero et al, 2018).…”
mentioning
confidence: 99%